2018
DOI: 10.1021/acs.jpcb.8b03456
|View full text |Cite
|
Sign up to set email alerts
|

Combining Freezing Point Depression and Self-Diffusion Data for Characterizing Aggregation

Abstract: The colligative property freezing point depression is evaluated as a means for estimating the extent of aggregation for solutions of poly(ethylene oxide) alcohol (CE) nonionic surfactant in cyclohexane. Combined with additional measurements of self-diffusion coefficients, it is shown that both unaggregated CE as well as reverse micelles are significantly present for the entire range of measured CE concentration (0.048-2.35 mol kg). A change in speciation near 0.2 mol kg is indicated by the results from both fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 43 publications
(87 reference statements)
1
14
0
Order By: Relevance
“…The results from this study confirm the prior findings on the binary system C 10 E 6 in cyclohexane (no water added) that the Stokes−Einstein equation fails to provide reasonable aggregate radii for this reverse micelle-forming system. 17 This finding was attributed to a change in mass-transport process from the movement of the small reverse micelles at low surfactant concentration to individual C 10 E 6 molecules jumping from reverse micelle to reverse micelle at high surfactant concentration. Additional insights can be derived from the observation in this study that the cyclohexane self-diffusion coefficient is independent from the amount of present water.…”
Section: ■ Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The results from this study confirm the prior findings on the binary system C 10 E 6 in cyclohexane (no water added) that the Stokes−Einstein equation fails to provide reasonable aggregate radii for this reverse micelle-forming system. 17 This finding was attributed to a change in mass-transport process from the movement of the small reverse micelles at low surfactant concentration to individual C 10 E 6 molecules jumping from reverse micelle to reverse micelle at high surfactant concentration. Additional insights can be derived from the observation in this study that the cyclohexane self-diffusion coefficient is independent from the amount of present water.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The latter are plotted in Figure 6 The aggregation numbers for 0% added water reproduce the values reported in our previous study. 17 Vasilescu et al reported for the reverse micellar system of 15% C 12 E 4 in cyclohexane at 8 °C an average aggregation number of 45 when 1% by mass water was added and 67 when 2% by mass water was added. 14 The concentration of 15% C 10 E 6 in cyclohexane was chosen for this study to facilitate comparison with these results.…”
Section: The Journal Of Physical Chemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…[49,50], and Baniani et al this issue). These nuclei offer, with the increase of their electron shell, the additional advantage of facilitating high-resolution measurement, with the option to selectively determine the diffusivity of each individual component in mixtures [38,[50][51][52]] to which we shall refer in more detail in Sects. 4.6 and 4.7.…”
Section: Limitations Modifications Pitfalls and Checks Of Consistencymentioning
confidence: 99%